SYNDROME OF RESISTANCE TO THYROID HORMONE - Miao, Tan Jia (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Resistance to thyroid hormone (RTH) is a rare genetic disorder characterized by clinically mild hyperthyroidism and biochemically elevated circulating free thyroid hormone levels with unsuppressed serum thyroid stimulating hormone. Here we reported the case of a 18-year-old male who was previously under paediatric follow-up for hyperthyroidism but with non-suppressed thyroid stimulating hormone (TSH). When treated with anti-thyroid drug, his thyroid hormone levels normalized but TSH increased, suggesting thyroid resistance. CASE We present a case of an 18-year-old male who was under paediatric follow-up since infancy. His mother was diagnosed with hyperthyroidism during her third pregnancy, and she underwent radioactive ablation after delivery. His initial cord T4 was 124 nmo/L (124- 244 nmol/L), and subsequent serial thyroid function tests revealed persistently high free T4 (FT4), so he was started on propylthiouracil at the age of 1 year and 8 months. After starting an antithyroid medication, his TSH became elevated while his FT4 returned to normal. His TSH returned to normal and FT4 increased after discontinuing the anti-thyroid medication. Even with elevated FT4 and non-suppressed TSH, he remained euthyroid. Clinically, there was no goitre. All systemic examinations, including his mental development and learning, were normal. His thyroglobulin antibody and thyroid microsomal antibody were positive. Neck ultrasound and TSH receptor antibody levels were both normal. Magnetic resonance imaging of the pituitary revealed no evidence of pituitary adenoma. Because the patient was asymptomatic, the decision was made to discontinue carbimazole. He remained asymptomatic despite having an FT4 in the upper range. Thyroid hormone resistance syndrome was eventually diagnosed. We had our limitations to further workup because the genetic test was not available in our country. He has not needed any antithyroid medication since then. CONCLUSION This case demonstrates not all hyperthyroidism must be treated with antithyroid medications. Early recognition could avoid unnecessary treatment.